An empirical study on environmental impact of natural draft cooling tower with flue gas injection. Issue 1 (1st January 2018) - Su, Shenshen; Zhang, Renfeng; Ma, JiJun; Xie, Yongping; Sun, Xijin; Han, Jianhua
Abstract: In order to understand the influences of natural draft cooling tower (NDCT) with flue gas injection on pollutant concentrations of the theoretical plume downwash area, an automatic air quality monitoring station was set in the theoretical plume downwash area of NDCT in Qinling power plant to get hourly SO2 and NO2 concentrations over a year. The results show that: 100% 1h average concentrations of SO2 and 99.64% NO2 observations satisfied the requirements of Chinese ambient air quality standard. High pollutant concentrations caused by plume downwash of NDCT with flue gas injection are not observed during the monitoring period, and there are no significant differences ( P > 0.05) between pollutant concentrations in the theoretical plume downwash area under the prevailing westerly wind conditions (37.2 ± 24.8 μg/m 3 ) and easterly wind conditions (36.9 ± 22.3 μg/m 3 ), while the concentrations under conditions of west wind speed > 5m/s are significantly lower ( P < 0.01) than those under conditions of west wind speed < 1.2m/s. The observations of this study indicate that ground pollutants at high concentration owing to plume downwash would not occur in the theoretical plume downwash area of NDCT with flue gas injection.